2018
DOI: 10.1002/elsc.201700174
|View full text |Cite
|
Sign up to set email alerts
|

Purification of bacterial inulinase in aqueous two‐phase systems

Abstract: In this study, extracellular inulinase from Bacillus sp. 11/3 was partially purified and concentrated using aqueous two‐phase system (ATPS). Two different phase forming salts and four types of polyethylene glycol (PEG) were used. Binodal curves and tie‐length lines (TLLs) for eight ATPS were developed. For inulinase purification, concentrations of PEG and salt according to binodal curves (between 17 and 26%) were chosen. All ATPSs for inulinase purification were characterized. An ATPS consisted of 26% PEG1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The normalized activity and stability of free and immobilized enzyme calculated for the same amount of enzyme has been evaluated under the same conditions in a wide range of pH (3.0-10.7); the results are shown in the Figure 5A and B. As reported in our previous study [46], the pH profile of the partially purified PEG phase free enzyme exhibits two peaks of optimal pH at 8 and 5.8, suggesting that the inulinase is present in two multiple forms. pH profile for the partially purified immobilized inulinase on the f-MWCNT prepared in this study also showed two pH optimums at 3.6 and 10 with the corresponding activity of 3.48 and 4.14 U/mg, respectively ( Figure 5A).…”
Section: Effect Of Ph On Immobilized Inulinase Activity and Stabilitymentioning
confidence: 71%
See 2 more Smart Citations
“…The normalized activity and stability of free and immobilized enzyme calculated for the same amount of enzyme has been evaluated under the same conditions in a wide range of pH (3.0-10.7); the results are shown in the Figure 5A and B. As reported in our previous study [46], the pH profile of the partially purified PEG phase free enzyme exhibits two peaks of optimal pH at 8 and 5.8, suggesting that the inulinase is present in two multiple forms. pH profile for the partially purified immobilized inulinase on the f-MWCNT prepared in this study also showed two pH optimums at 3.6 and 10 with the corresponding activity of 3.48 and 4.14 U/mg, respectively ( Figure 5A).…”
Section: Effect Of Ph On Immobilized Inulinase Activity and Stabilitymentioning
confidence: 71%
“…Inulinase was produced by submerged fermentation of Bacillus sp. 11/3, as described in Temkov et al [46]. The enzyme was partially purified by ATPS and then immobilized onto MWCNTs.…”
Section: Practical Applicationmentioning
confidence: 99%
See 1 more Smart Citation